Analisis kandungan nitrogen dan fosfor pada sedimen Danau Tondano di area budidaya Toulimembet - Telaumbanua, Yedieli; Tumembouw, Sipriana S.; Watung, Juliaan Ch.; Undap, Suzanne L.; Pangemanan, Pankie L.; Longdong, Sammy N.J. (Universitas Sam Ratulangi, 2023)
The aim of the research was to analyze the nitrogen and phosphorus content in sediments in the cultivation area of Toulimembet Village. This research method is